Trauma and the Hero’s Mind: A Freudian Ego Analysis of Bruce Wayne in The Batman - Syarif, Ahmad; Purnomo, Budi (International Journal of English Linguistics, Literature, and Education (IJELLE), 2025)
This study examines Bruce Wayne’s psychological dynamics in The Batman (2022) using Sigmund Freud’s psychoanalytic theory, with a focus on the ego’s role in mediating trauma and moral conflict. This study analyzes how Wayne’s unresolved childhood trauma and dual identity as a vigilante reflect the interplay between the id, ego, and superego. Employing a qualitative descriptive method, this study analyzes purposively selected scenes and dialogues from The Batman using close textual analysis. Audience reception data further support the interpretation of Wayne’s character as a psychologically complex figure. The findings reveal that Wayne’s ego adapts to internal and external pressures through ethical compromises, illustrating Freud’s theory of ego functioning. This study contributes to contemporary literary and film criticism by offering a psychoanalytic perspective on trauma and identity in modern superhero narratives.